The Insulin Receptor: A New Target for Cancer Therapy - Belfiore, Antonino; Malaguarnera, Roberta (Frontiers in Endocrinology, 2011)
A large body of evidences have shown that both the IGF-I receptor (IGF-IR) and the insulin receptor (IR) play a role in cancer development and progression. In particular, IR overactivation by IGF-II is common in cancer cells, especially in dedifferentiated/stem-like cells. In spite of these findings, until very recently, only IGF-IR but not IR has been considered a target in cancer therapy. Although several preclinical studies have showed a good anti-cancer activity of selective anti-IGF-IR drugs, the results of the clinical first trials have been disappointing. In fact, only a small subset of malignant tumors has shown an objective response to these therapies. Development of resistance to anti-IGF-IR drugs may include upregulation of IR isoform A (IR-A) in cancer cells and its overactivation by increased secretion of autocrine IGF-II. These findings have led to the concept that co-targeting IR together with IGF-IR may increase therapy efficacy and prevent adaptive resistance to selective anti-IGF-IR drugs. IR blockade should be especially considered in tumors with high IR-A:IGF-IR ratio and high levels of autocrine IGF-II. Conversely, insulin sensitizers, which ameliorate insulin resistance associated with metabolic disorders and cancer treatments, may have important implications for cancer prevention and management. Only few drugs co-targeting the IR and IGF-IR are currently available. Ideally, future IR targeting strategies should be able to selectively inhibit the tumor promoting effects of IR without impairing its metabolic effects.